2015
DOI: 10.1007/s00436-015-4365-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Babesia-responsive leucine-rich repeat domain-containing protein from the hard tick Haemaphysalis longicornis

Abstract: Haemaphysalis longicornis is a tick known for transmitting Babesia parasites, including Babesia gibsoni, in East Asian countries. The vector tick must have strategies to control Babesia parasites, while Babesia parasites are also considered to establish an evasive mechanism from the tick's innate immunity. Due to this mutual tolerance, H. longicornis is considered to be a vector of Babesia parasites. Recent studies have shown the important roles of leucine-rich repeat (LRR) domain-containing proteins in innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It could be shown that LRR domain-containing proteins were upregulated in the salivary gland and midgut of the infected tick Haemaphysalis longicornis during blood feeding. It is stated that LRRs play a key role in the tick innate immunity in controlling Babesia parasites [78]. Analogous to this, a possible function of LRRs in venom glands could be protection against undesired microbes that might invade spiders after injecting venom into an organism (Supplementary Figure S1.19).…”
Section: Resultsmentioning
confidence: 97%
“…It could be shown that LRR domain-containing proteins were upregulated in the salivary gland and midgut of the infected tick Haemaphysalis longicornis during blood feeding. It is stated that LRRs play a key role in the tick innate immunity in controlling Babesia parasites [78]. Analogous to this, a possible function of LRRs in venom glands could be protection against undesired microbes that might invade spiders after injecting venom into an organism (Supplementary Figure S1.19).…”
Section: Resultsmentioning
confidence: 97%
“…H. longicornis is easy to maintain and is widely used as a model tick to study pathophysiology in tick infestation33. To date, a number of bioactive molecules have been found in H. longicornis , and those products might be available for not only tick control but also for novel drug discovery in the veterinary and medical fields78343536. The experimental infection of ticks with pathogens is considered to be an attractive tool for studying tick-pathogen interaction56.…”
Section: Discussionmentioning
confidence: 99%
“…The WT open reading frame sequence was amplified by PCR using a forward primer (HlPrx2 F‐ Xho I) containing an Xho I recognition site and a reverse primer (HlPrx2 R‐ Eco RI) containing an Eco RI recognition site (Table ). The amplified PCR product was then purified using a GENECLEAN ® II KIT (MP Biomedical, Solon, OH, USA) and subcloned into the frame of the pRSET C. The WT was expressed in the Escherichia coli BL21 (DE3) strain and purified as described previously (Maeda et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The WT open reading frame sequence was amplified by PCR using a forward primer (HlPrx2 F-XhoI) containing an XhoI recognition site and a reverse primer (HlPrx2 R-EcoRI) containing an EcoRI recognition site ( Table 1). The amplified PCR product was then purified using a GENECLEAN V R II KIT (MP Biomedical, Solon, OH, USA) and subcloned into the frame of the pRSET C. The WT was expressed in the Escherichia coli BL21 (DE3) strain and purified as described previously (Maeda et al, 2015). To prepare the mutated proteins, inverse PCR of the plasmid DNA (pRSET C containing HlPrx2 WT) was performed by using mutation primers and KOD-Plus-Neo (TOYOBO, Osaka, Japan) following the manufacturer's protocol for a single nucleotide substitution (Table 1).…”
Section: Expression and Purification Of Wild-type Recombinant Hlprx2 mentioning
confidence: 99%